Soluble Programmed Death Receptor Ligands sPD-L1 and sPD-L2 as Liquid Biopsy Markers for Prognosis and Platinum Response in Epithelial Ovarian Cancer - Buderath, Paul; Schwich, Esther; Jensen, Christina; Horn, Peter A.; Kimmig, Rainer; Kasimir-Bauer, Sabine; Rebmann, Vera (Frontiers in Oncology, 2019)
Introduction: Response to platinum-based therapy is a major prognostic factor in epithelial ovarian cancer (EOC) and reliable prognostic biomarkers are urgently needed to identify patients at high risk. Since ligands of the Programmed Death Receptor-1 (PD-L1 and PD-L2) play a crucial role within the tumor microenvironment for tumorigenesis, we investigated levels of sPD-L1 and sPD-L2 in liquid biopsies of serum samples, and correlated the results with the clinical status, presence of circulating tumor cells (CTCs) and disease outcome in primary EOC patients. Methods: sPD-L1 and sPD-L2 were determined by ELISA in patients (N=83) and healthy females (N=29). Gene expression analysis of EpCAM, MUC-1, CA-125, and ERCC1 was performed by RTPCR after CTCs enrichment. Results: sPD-L1 was significantly (p=0.0001) increased and sPD-L2 decreased (p=0.003) in EOC patients compared to controls. While enhanced sPD-L1 was associated with residual tumor burden (p=0.022), reduced sPD-L2 levels were related with platinum-resistance (p<0.01) and the presence of ERRC1+ CTCs (p<0.0001). High sPD-L1 levels were associated with a reduced 5-year overall survival (OS, p=0.003) and progression-free survival (PFS, p=0.019). Strikingly, sPD-L1 levels >6.4 pg/ml were indicative for a reduced OS (p=0.035) and PFS (p=0.083) in platinum-sensitive patients, while OS and PFS in platinum-resistant patients did not differ when patients were stratified to this cut-off. Conclusions: Our study highlights sPD-L1 and sPD-L2 as complementary biomarkers reflecting clinical status, treatment response and disease outcome of EOC patients. Especially, sPD-L1 may facilitate to identify high risk patients with unfavorable disease outcome despite platinum-sensitivity arguing for additional therapeutic approaches. As sPD-L1 and sPD-L2 are easily accessible via liquid biopsy, the inclusion of sPD-L1 and sPD-L2 in addition to CTC investigation as markers for risk assessment during patient therapy planning and follow-up appears to be a valuable approach.